Aging Process of Cadmium, Copper, and Lead under Different Temperatures and Water Contents in Two Typical Soils of China. (28th May 2020) - Liu, Guannan; Yu, Zhanqiu; Liu, Xinhui; Xue, Wei; Dong, Liming; Liu, Yongbing
Abstract : Aging process of exogenous heavy metals in soil is significant for reducing their environmental risk due to the redistribution of species of soil heavy metals. A red soil (ultisol) and a brown soil (alfisol) were selected to investigate the aging process of cadmium (Cd), copper (Cu), and lead (Pb) under different regimes of temperature and water content. Most introduced heavy metals were all transformed from dissolved fraction to more stable fractions within 5 days of incubation. During incubation, most Pb existed in the fraction bound to Fe/Mn oxides, while exchangeable and carbonate-associated fraction was the dominant portion for Cd and Cu, suggesting that the transformation rate followed the order: Pb > Cu > Cd. The exchangeable and carbonate-associated fraction in red soil, which was characterized with higher pH and Fe/Al/Mn oxides and lower organic matter (OM), was significantly higher than that in brown soil, implying that soil OM was the important factor affecting the aging process of soil heavy metals in the present study. In addition, increases of temperature and soil water content can accelerate the transformation of most introduced Cd, Cu, and Pb to more stable forms in the soils. The results indicated that soil properties, environmental factors (i.e., temperature and water content), types of heavy metals, and pollution time can significantly affect the aging process of exogenous heavy metals.